Simultanagnosia as the presenting symptom in neuro-ophthalmology. Issue 1 (2nd January 2020) - Wang, Rui; Hopping, Grant; Al Othman, Bayan; Tabba, Subhan; Kini, Ashwini; Lee, Andrew G.
Abstract: Simultanagnosia is a well-known neurologic symptom characterized by the inability to conceptualize the whole picture despite being able to see individual elements within a visual scene. The pathophysiology involves a lesion to the bilateral parieto-occipital lobe. We report two unusual cases of simultanagnosia and juxtaposed homonymous visual field loss involving aqueductal stenosis–related obstructive hydrocephalus and cardiac arrest due to Brugada syndrome. Clinicians should be aware that simultanagnosia can be the presenting symptom of neuro-ophthalmic disease.